The Effectivness of the Computer Misuse Act in Addressing Cyber Crimes in Uganda - Timothy Ahimbisibwe (Uganda Christian University, 2024)
This research is going to mainly focus on the cybercrimes in Uganda. It will also look at the Effectiveness of the computer Misuse Act in addressing Cybercrimes in Uganda as well as the amendment act of 2022. The research will also look at the different Statues that have come up to combat cybercrimes in Uganda. Different literatures are going to be reviewed in order to come up with an effective research paper in order to help in addressing cybercrimes in Uganda. The study conducted to check the effectiveness of the Uganda computer Misuse Act found that through the results of desk reviews, interviews and investigations indicated that some articles in the computer misuse Act involved very many cybercrimes, however most of the cybercrimes are general and do not go in depth on how the act is enforced and the amount of penalty given to liable criminals. Different recommendations shall be made in a way to fill in the gaps that have been left in the fight against cybercrimes.